The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s10886-011-9964-x
|View full text |Cite
|
Sign up to set email alerts
|

New Sex Pheromone Blend for the Lightbrown Apple Moth, Epiphyas postvittana

Abstract: The composition of the sex pheromone gland of the lightbrown apple moth, Epiphyas postvittana (Walker) was re-investigated. In addition to the two previously identified compounds, (E)-11-tetradecenyl acetate (E11-14Ac) and (E,E)-9,11-tetradecadienyl acetate (E9E11-14Ac), seven additional candidate pheromone compounds were identified: (E)-11-tetradecen-1-ol (E11-14OH), tetradecyl acetate, hexadecanal, (E)-11-hexadecenyl acetate (E11-16Ac), hexadecyl acetate, octadecanal, and octadecyl acetate. Gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…Although a more attractive synthetic lure is now available (El-Sayed et al 2011), even the two-component blend was more than twice as attractive as single virgin females in this study, because of the high loading of 3 mg. Use of the highly attractive four-component blend or a high loading of two components (as here) raises the complication of underestimating efÞcacy of disruption compared with females, although synthetic lures are easier to use. The relatively similar results for both virgin females and two-component synthetic lures makes this comparison straightforward here.…”
Section: Discussionmentioning
confidence: 74%
“…Although a more attractive synthetic lure is now available (El-Sayed et al 2011), even the two-component blend was more than twice as attractive as single virgin females in this study, because of the high loading of 3 mg. Use of the highly attractive four-component blend or a high loading of two components (as here) raises the complication of underestimating efÞcacy of disruption compared with females, although synthetic lures are easier to use. The relatively similar results for both virgin females and two-component synthetic lures makes this comparison straightforward here.…”
Section: Discussionmentioning
confidence: 74%
“…Tumlinson et al 1989,1994; Vickers et al 2003; Domingue et al 2007, 2008; Kanno et al 2010; El-Sayed et al 2011; Leary et al 2012; Martin et al 2013), our finding that 24% of the sampled, pheromone-responsive protocerebral neurons in this study did not distinguish among the tested stimuli (supplemental Table 1) is surprising. Pairwise comparisons of responses to different pheromonal stimuli (EEZ vs. BAL, EEZ vs. mixture, BAL vs. mixture) showed that 50–80% of neurons exhibited no significant differences in their responses to these stimulus pairs (Figure 1, bottom).…”
Section: Discussionmentioning
confidence: 52%
“…A widely used continuous fixed-bed-column model was established by Bohart and Adams, who assumed that the rate of adsorption is controlled by the surface binding (through chemical reaction or physical interaction) between adsorbate and unused capacity of the solid, i.e., adsorption rate = K·C·Cu, where K is the adsorption rate coefficient, C is the adsorbate concentration at the solid phase at distance x, and Cu is the unused surface adsorptive capacity at time t, expressed as mass per volume of bed [10,12]. The material balance for adsorbate is given by the partial differential equation:…”
Section: Resultsmentioning
confidence: 99%